Polymorphism of the trehalase gene (TREH) in native populations of Siberia - B. A. Malyarchuk; M. V. Derenko (Вавиловский журнал генетики и селекции, 2018)
Deficiency of some carbohydrates in the traditional diet of native populations of the Far North contributed to a high population prevalence of inactive variants of genes encoding, for example, amylase (AMY2A gene) and sucraseisomaltase (SI gene). Trehalose, which is found in algae, higher fungi, lichens and some higher plants, is another of the disaccharides, poorly digested by native people of the Far North. Here, in native populations of Siberia, we studied the polymorphism of the TREH gene, which encodes trehalase, an enzyme that cleaves trehalose. The analysis of exome polymorphism showed the presence of seven haplotypes of the TREH gene in the population. Three of them are determined by the variant rs2276064A, which is associated with the lowest activity of trehalase. The maximum frequency of this group of haplotypes is observed in the samples of native populations of Northeast Asia (about 60 %), in the remaining samples of the Siberian populations, its frequency is 30–40 %. Thus, the high frequency of variant rs2276064A, associated with a lowactivity trehalase, explains why Northern aboriginal peoples avoid food containing trehalose. It is assumed that the increase in the frequency of this variant in the populations of Northeast Asia can have been facilitated by gene drift acting in populations of a small effective size. However, it is possible that artificially induced trehalose deficiency in the traditional diet of the indigenous peoples of the Far North (due to the tradition of rejecting fungi) could also cause an increase in the frequency of lowactivity trehalase, provided that this tradition has been existing among Northern aboriginal peoples for many generations.